THE CATEGORY OF MODALITY IN COMPARATIVE LINGUISTICS: RESEARCH AND INTERPRETATION (BASED ON THE EXAMPLE OF FRENCH AND UZBEK FAIRY TALES) - Matyakubov, Oybek (Foreign Languages ​​in Uzbekistan (JOURNALFLEDU.COM), 2024)
This article highlights the use and expression of the modality category in linguistics, researches its theoretical foundations, and examines the relevance of the work. Scientific studies on the category of modality existing in linguistics are analyzed, the theoretical views of scientists are put into one system, and the category of modality is defined. The functionalsemantic category of modality is considered a comprehensive research object, and its main essence and function, together with the person and tense category, form the main parts of the sentence and play an important role in expressing the speaker’s attitude to real existence. Axiological modality is essential in revealing the subjective-modality features and the emotional-expressive content of a sentence, analysing the texts’ linguocognitive features, the textual modality issues, etc.